PENERAPAN TEKNOLOGI PENGOLAHAN PAKAN FERMENTASI BAGI KELOMPOK TERNAK ITIK DI KELURAHAN LANDASAN ULIN B ARAT KECAMATAN LIANG ANGGANG KOTA BANJARBARU - Siti Dharmawati; Nordiansyah Firahmi M; Syarif Djaya (Universitas Islam kalimantan MAB, 2015)
This activity involves two groups , that is Tani Farmer's Group Work Kalbuja and Farmer's Group Karya Tani. The main problem faced by the two groups of farmers related to feed processing technology and maintenance management intensive duck . The purpose of this activity is to provide training , demonstration and application of appropriate technology in terms of maintenance management intensive duck - feed and local feed processing.. The method used is counseling , training and assistance to members of farmer groups as partner. The results showed that the activities of members of the farmers who are very enthusiastic partner and give a very positive response to the activities offered . This success indicator is able to implement a maintenance management breeder ducks , able to process quality and production of duck feed produced quite high ( 2.25 to 2.75 kg / ) and feed conversion of 2.25 -2.30 . Implikaai of this activity is 20 % of the members of the group independently partners have been able to expand its business , namely the maintenance intended for ranged from 100 to 350 male ducks, and 100-200 laying ducks.